Evaluating the Effectiveness of Nonwoven Geotextile-Encased Cinder Gravel Column in Improving Load-Bearing and Deformation Characteristics of Soft Clay - Narob Kifle Tefera; Damtew Tsige Melese; Habte Tamirat Bafena; Adamu Beyene Negesa (Advances in Materials Science and Engineering)
Application of vertically installed columnar materials made of natural gravels or crushed aggregate is one of the commonly implemented practices to improve the performance of soft clay grounds under footing load. Alternative materials like cinder gravel also plays a reinforcing role when blended with soft clay. However, information on the precise extent to which a vertically installed cinder gravel column is effective in improving the properties of a clay foundation and its potential response to the permanently applied footing load has not been well documented in the literature. Hence, the current study specifically aimed at evaluating the effectiveness of geotextile-encased cinder gravel column in improving deformation and bearing capacity of soft clay ground. The experimental model which considered installation of a single geotextile-encased cinder gravel column into soft clay was considered. A cylindrical steel container was used in designing the experimental test. The container was filled with clay soil and the cinder gravel column was vertically installed through a replacement method. Finding of the study revealed that ultimate load-bearing capacity of the soft clay foundation after being reinforced with conventional cinder gravel was 1.85 times that of the untreated soft clay soil. The load-carrying capacity of the clay soil decreased with increment in diameter of the column whereas it is directly related to the volume replacement ratio. With regard to directional improvement, the vertical reinforcement performs better than the horizontal geotextile strips in cinder gravel column from bearing capacity improvement view point. In lessening settlement, however, application of horizontal geotextile discs at spacing ranging between half- and full-column diameter overweighs performance of the vertical encasement. In summary, application of geotextile encasement to the top 75% of the clay thickness is sufficient to come up with optimum improvement in bearing capacity and encasing the entire thickness is not necessarily required.